(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
This study presented the recovery of uranium oxide and thorium oxide from aluminothermic slag from the metallurgical processing of columbite – a niobium/tantalum mineral with the presence of U3O8 and ThO2 – from a mining-industrial facility. The methodology consisted of sampling, comminution, and leaching using sulfuric acid. The head sample showed contents of (1.78 + 0.14) % for U3O8 and (3.66 + 0.04) % for ThO2. The metallurgical recovery reached values above 80% for the uranium oxide and above 70% for the thorium oxide for pH < 1.5 and process time greater than eight hours.